Acute and long-term success of ventricular tachycardia ablation in patients with ischemic heart disease in a Mexican center - Cueva-Parra, Angel (2022)
Objective. To report the results of ventricular tachycardia (VT) catheter ablation in ischemic heart disease (IHD), and to identify risk factors associated with recurrence in a Mexican center. Materials and methods. We made a retrospective review of the cases of VT ablation performed in our center from 2015 to 2022. We analyzed the characteristics of the patients and those of the procedures separately and we determined factors associated with recurrence. Results. Fifty procedures were performed in 38 patients (84% male; mean age 58.1 years). Acute success rate was 82%, with a 28% of recurrences. Female sex (OR 3.33, IC 95% 1.66–6.68, p=0.006), atrial fibrillation (OR 3.5, IC 95% 2.08–5.9, p=0.012), electrical storm (OR 2.4, IC 95% 1.06–5.41, p=0.045), functional class greater than II (OR 2.86, IC 95% 1.34–6.10, p=0.018) were risk factors for recurrence and the presence of clinical VT at the time of ablation (OR0.29, IC95% 0.12–0.70, p=0.004) and the use of more than 2 techniques for mapping (OR 0.64, IC 95% 0.48–0.86, p=0.013) were protective factors. Conclusions. Ablation of ventricular tachycardia in ischemic heart disease has had good results in our center. The recurrence is similar to that reported by other authors and there are some factors associated with it.